The practice of knowledge sharing among academicians in UiTM Terengganu / Sabiroh Md.Sabri, Siti Hajar Wan Mohammad and Rozita Mengen - Md.Sabri, Sabiroh; Wan Mohammad, Siti Hajar; Mengen, Rozita (2012)
For more than a decade, knowledge has been recognized as one of the important resources that contribute to the competitive advantage of an organization. Literature agreed that the sustainability of an organization is very much depending on how well knowledge in the organization is managed. The success of knowledge management relies on social interaction and organizational culture which encourage knowledge capture, sharing or transfer between individuals and reuse them. However, it is interesting to learn that, in higher learning institution where academicians hold some types of knowledge in high regards; academic knowledge significantly remains a “cottage industry” with both tacit and explicit knowledge kept isolated within the academician’s guilds. Knowledge generated by research activities always stay within the academic community, rarely crosses disciplinary boundaries and far away from reaching the industry community. True, there has always been academic collaboration among academicians, but there is little systematic sharing of learning content, context and supporting materials. Therefore, it is the challenge of institutional leadership to work on how knowledge can be understood and shared in different ways among the academicians inside and outside the organization. This research attempts to investigate the practice of knowledge sharing among academicians in Universiti Teknologi MARA Terengganu (UiTMT). Knowledge sharing has been identified as a part of Critical Success Factor in the implementation of knowledge management in an organization. The knowledge sharing practice was measured through the implementation of SECI model introduced by Nonaka and Takeuchi (1995) which facilitate the interaction of four knowledge-creating processes which also described the ways knowledge is generated, transferred and re-created in organizations. Data was collected through self-administered questionnaires distributed to 205 UiTMT’s lecturers selected using quota sampling. Data was analysed using descriptive statistics to determine the level of practice of knowledge sharing among academicians. Results shown that academicians in UiTMT practice knowledge sharing at moderate level. Furthermore, the results also shown that there is no significant difference in knowledge sharing practice between different position levels. The results of this study will be used to help the management of UiTMT strategize the knowledge management implementation in the future.